Magnetic molecularly imprinted polymers (MMIPs): synthesis and characterization for the spectrophotometric determination of caffeine - Ali, Shahab (2019)
Daily food items contain considerable amount of caffeine that is constantly released to the environment, causing major problems to living organisms that can shift the entire ecosystem resulting adverse public health and the environment. Secondly, many market samples of caffeinated products have found with extremely high amounts of caffeine to toxic level (300 mg – 400 mg) that must be regulated by rapid techniques to assure human health and safety. An alternative method for the detection and quantification is the development of biomimetic sensors, using magnetic molecularly imprinted polymers (MMIPs) like sensing phase. The advantages of molecular imprinted materials are high selectivity, sensitivity and stability, and low cost. This work aimed to develop an efficient method of preparation of core-shell magnetic nanoparticles (MNPs) modified with molecularly imprinted polymers (MIPs) used as selective material, in order to determine caffeine in the food samples in a very smart magnetic fashion. Metacrylic acid (MAA) was used as functional monomers; ethylene glycol dimethacrylate (EGDMA) was used as cross-linking reagents, 2,2'-azo-bis isobutironitrila (AIBN) as a radical initiator and ethanol as pororgenic solvent. Magnetic molecularly non-imprinted polymers (MNIPs) which served as a control for comparative studies, synthesized along with MMIPs. Characterizations of MMIPs and MNIPs were performed by Vibrating sample magnetometry (VSM), Fourier Transform Infra-Red (FTIR) and Transmission Electron Microscopy (TEM). The adsorption capacity and selectivity of the materials were studied in detail, from the respective adsorption isotherms and its kinetics. The adsorption data was well described by Langmuir-Freundlich isotherm model with adsorption equilibrium constant (K) of 9.6 x 102 mol L-1 which is higher in comparison with the reported. The selectivity experiments revealed that prepared MMIP had higher selectivity toward caffeine compared to other molecules with comparable chemical structures of theophylline and xanthine